#### Answer

$3$

#### Work Step by Step

To find the value of $f(\frac{1}{3})$, substitute $\frac{1}{3}$ to $x$ in $f(x)$ to obtain:
$f(x)=-3x+4
\\f(\frac{1}{3})=-3(\frac{1}{3})+4
\\f(\frac{1}{3}) = -1+4
\\f(\frac{1}{3}) = 3$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.